2015
DOI: 10.1016/j.aap.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Media reporting of traffic legislation changes in British Columbia (2010)

Abstract: BC's new traffic laws generated considerable media attention both pro and con. We believe that this media attention helped inform the public of the new laws and enhanced their deterrent effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…During the past few decades, various left-turn designs have been used on urban intersections to reduce problems accompanying direct left-turn (DLT) vehicles. The difficulty of completing this movement is evident in crash statistics, indicating that 45% of all crashes that occur at intersections throughout the United States involve left-turning vehicles, even though left-turning movements represent a disproportionately small percentage (10–15%) of all approaching traffic [ 10 , 11 ]. DLT vehicle movements from arterial streets or collector roads are prohibited by using non-crossing median and/or directional median openings.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, various left-turn designs have been used on urban intersections to reduce problems accompanying direct left-turn (DLT) vehicles. The difficulty of completing this movement is evident in crash statistics, indicating that 45% of all crashes that occur at intersections throughout the United States involve left-turning vehicles, even though left-turning movements represent a disproportionately small percentage (10–15%) of all approaching traffic [ 10 , 11 ]. DLT vehicle movements from arterial streets or collector roads are prohibited by using non-crossing median and/or directional median openings.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of media coverage for a certain issue has been proven to seed its perceived importance among the public [ 33 ]. Some of the previous research papers observed that media coverage can increase public awareness [ 38 , 39 ] and may result in behavioural change [ 40 ]. This study aimed to review the media coverage of inattention in road traffic and to analyse how the Czech media use their potential to shape public opinion and risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…Various left turn designs have been used in urban intersections to reduce problems accompanying DLT vehicles [19, 20]. The difficulty of completing a left turn is evident in crash statistics, which indicate that 45 percent of all crashes that occur at intersections throughout the United States involve left-turning vehicles, even though left-turning movements represent a disproportionately small percentage (10-15 percent) of all approaching traffic [21, 22]. DLTs from main streets or branch roads are prohibited by the use of a noncrossing median and/or directional median openings [23].…”
Section: Introductionmentioning
confidence: 99%